Advertisement Remove all ads

Solve the Following Equation : Ax2 + (4a2 - 3b) X - 12ab = 0 - Mathematics

Sum

Solve the following equation : `"ax"^2 + (4"a"^2 - 3"b")"x" - 12"ab" = 0`

Advertisement Remove all ads

Solution

`"ax"^2 + (4"a"^2 - 3"b")"x" - 12"ab" = 0`

`"x"^2 + 4"ax" - 3  "b"/"a" "x" - 12 "b" = 0`

`"x"("x" + 4"a") - 3  "b"/"a" ("x" + 4"a") = 0`

`("x + 4a")("x" - 3  "b"/"a") = 0`

x = -4a , x = `3  "b"/"a"`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Frank ICSE Class 10 Mathematics Part 2
Chapter 6 Quadratic Equations
Exercise 6.1 | Q 17
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×